Physiological effects of technique and rolling resistance in uphill roller skiing - Hoffman, M. D.; Clifford, P. S.; Snyder,A. C.; O'Hagan, K. P.; Mittelstadt, S. W.; Roberts, M. M.; Drummond, H. A.; Gaskill, S. E. (Medicine & Science in Sports & Exercise, 1998)
The double pole technique (DP) has been shown to be more economical than the V1 skate technique (V1) on flat terrain. The objective of the present study was to compare these two techniques during uphill roller skiing. In addition, the physiological effects of changing roller ski rolling resistance was examined for V1. The findings suggest that 1) grade has little effect on relative economies of DP and V1, possibly because of a lower effectiveness of force application with V1 when going uphill, and 2) large differences in roller ski rolling resistance should have no effect on the cardiovascular training adaptations that result from uphill roller skiing with V1.